2003
DOI: 10.1080/0264041031000101999
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle fatigue in swimmers after a single 200 m swim

Abstract: Inspiratory muscle fatigue may occur in as little as 6 min during high-intensity spontaneously breathing exercise. The aims of this study were to determine whether inspiratory muscle fatigue occurs during swimming exercise and whether inspiratory muscle strength differs between the supine and standing body positions. Seven competitive swimmers were recruited to perform a single 200 m front-crawl swim, corresponding to 90-95% of race pace. Inspiratory muscle strength was measured at residual volume using a hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
62
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 15 publications
10
62
0
1
Order By: Relevance
“…As such, applying the findings from this study to exercise-induced respiratory muscle fatigue necessitates caution. Nonetheless, the declines in maximal volitional mouth pressures in our highly motivated subjects following IVH were similar to, though slightly less than, those seen following exerciseinduced RMF (e.g., 10 and 7 % declines in MIP and MEP, respectively, in our subjects vs. 10-28 % in previous investigations) (Coast et al 1999;Cordain et al 1994;Lomax and Castle 2011;Lomax and McConnell 2003;Romer et al 2002). Moreover, the significant inverse correlations between change in MIP and ventilatory loads (i.e., total volume and time to fatigue) are in agreement with the concept that degree of muscular fatigue is related to muscular work, further implying that the volitional measure, despite its limitations (American Thoracic Society/European Respiratory 2002), was likely indicative of global respiratory fatigue.…”
Section: Methodological Considerationssupporting
confidence: 67%
“…As such, applying the findings from this study to exercise-induced respiratory muscle fatigue necessitates caution. Nonetheless, the declines in maximal volitional mouth pressures in our highly motivated subjects following IVH were similar to, though slightly less than, those seen following exerciseinduced RMF (e.g., 10 and 7 % declines in MIP and MEP, respectively, in our subjects vs. 10-28 % in previous investigations) (Coast et al 1999;Cordain et al 1994;Lomax and Castle 2011;Lomax and McConnell 2003;Romer et al 2002). Moreover, the significant inverse correlations between change in MIP and ventilatory loads (i.e., total volume and time to fatigue) are in agreement with the concept that degree of muscular fatigue is related to muscular work, further implying that the volitional measure, despite its limitations (American Thoracic Society/European Respiratory 2002), was likely indicative of global respiratory fatigue.…”
Section: Methodological Considerationssupporting
confidence: 67%
“…These measurements are noninvasive and have potential for the assessment of exercise-induced respiratory muscle fatigue, as demonstrated by the transient fall in pressures after high-intensity sustained exercise (82,100,101,187,317,452,547) and longer duration endurance exercise (93,107,223,316,455). The major limitation of maximal volitional pressures as measures of fatigue is that they are highly dependent on the subject's effort and therefore susceptible to changes in motivation or other central factors.…”
Section: Assessment Of Respiratory Muscle Fatigue Maximum Volitional mentioning
confidence: 98%
“…Wells and coworkers (Wells et al 2005) have shown that 12 weeks of CRMT can increase critical swimming speed in female, but not male, adolescent competitive swimmers, whereas Wylegala et al (Wylegala et al 2007) recently demonstrated that 4 weeks of respiratory muscle training improved swimming endurance in scuba divers. Interestingly, research on competitive Masters Swimmers has shown that a single 200 m freestyle swim corresponding to 90-95% of race pace was sufficient to induce inspiratory muscle fatigue (IMF) (Lomax and McConnell 2003). Whether this IMF developed during swimming (Lomax and shown to occur after the swim phase of a triathlon (Hill et al 1991).…”
Section: Implications For Swim Performancementioning
confidence: 99%